Economic estimation of boron isotope production by gas diffusion method using BF3 as processing gas. (December 2020) - Wang, Y B; Pei, G; Jiang, D J; Zhou, M S
Abstract: Natural occurring boron has two stable isotopes: boron-10 and boron-11. Boron-10 has high thermal neutron cross section in a wide range of energy and the product of boron-10's neutron reaction contains alpha particles. So, it is a good material for neutron absorbing and neutron detecting. In order to enrich boron-10 from natural boron, several methods had been proven to be feasible: chemical exchange distillation, cryogenic distillation and ion exchange resin method. The market now places higher demands on the economics of the separation method, so study on production of boron-10 by gas diffusion method is carried out. Using BF3 as processing gas, it is feasible to enrich high abundance of boron-10 by gas diffusion. The single stage separation effect and the hydraulic status of single stage was estimated. Binary gas diffusion cascades were designed and compared. Under given production requirements, the scale of the cascade was estimated and optimized. Finally, step cascade was picked for the production of 96% boron-10. Based on the cascade design, economic estimation of this separation method was conducted, and the target product cost was calculated. This study laid a good foundation for the expansion of boron isotope separation methods.